Tectonic and geology of the region of the juquitiba topografic sheet in 1:50.000, southeast of the state of sÃo paulo - Godoy, Antonio Misson [UNESP]; Oliveira, Marcos Aurélio Farias De [UNESP]; Hackspacher, Peter Cristian [UNESP]; Vieira, Otávio Augusto Ruiz Paccola [UNESP]; Manzano, Jefferson Cassu (My University, 2018)
Geological mapping of the Juquitiba Topographic Sheet lithological units in 1: 50.000 scale is the result of integration and realization of geological surveys. The area is located southwest of São Paulo city and inserted in the Central Mantiqueira Province, central portion of the Ribeira Belt. It comprises a small region, north of the Caucaia-Rio Jaguari Shear Zone, constituted by the Cotia Block rocks and, the largest area, by the Juquitiba Block rocks. The region contains metasedimentary migmatized rock lithotypes, migmatitos, gneiss and aluminous schists, in addition to amphibolites metasandstones and calcium-silicate rocks, all of Meso to Neoproterozoic age, belonging to the Embu Complex; numerous peraluminous S type granites and pegmatites bodies; Neoproterozoic I Type calc-alkaline granite bodies of the Ibiúna and Caucaia complexes; and recent quaternary sediments. The tectono-metamorphic evolution shows D1/2tangential deformations/progressive metamorphism, associated to collisional process, and D3 transcurrent/transpressive tectonics, NE-SW direction, marked by intense vertical milonitic foliation and smooth to open regional folds. The progressive regional metamorphism is of the Barrowian type, with high amphibolite facies rocks and contact metamorphism local, as the retrometamorphism caused by dynamic metamorphism nature.
GEOLOGIA E TECTÔNICA DA REGIÃO DA FOLHA TOPOGRÁFICA DE JUQUITIBA EM 1:50.000, SUDESTE DO ESTADO DE SÃO PAULO
Keywords: Embu Complex; Geological mapping; Juquitiba region; Paragneiss